2018
DOI: 10.5152/tao.2018.2987
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hard Palate Angulation Caused by Septal Deviation on Maxillary Sinus Volume

Abstract: Objective: To investigate the effect of hard palate angulation caused by septal deviation on the volume of the maxillary sinus. Methods:Coronal computed tomographic (CT) scans of 1568 patients aged from 18 to 60 were examined. CT scans of 402 patients were included in the study. On these scans, the maxillary sinus volume, the angle of the nasal septal deviation, and the angulation of the hard palate were calculated using the ImageJ software. Each maxillary sinus volume was statistically compared with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…In our study, we found an incidence of 74%. Sapmaz et al [6] found that nasal septal deviation leads to reduced maxillary sinus volume on the deviated side. Our results revealed no significant relation-ship between nasal septal deviation and infundibulum length or ostium height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found an incidence of 74%. Sapmaz et al [6] found that nasal septal deviation leads to reduced maxillary sinus volume on the deviated side. Our results revealed no significant relation-ship between nasal septal deviation and infundibulum length or ostium height.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal septal deviation, seen in about 80% of the population, is defined as an asymmetry of the nasal septum, and it may limit air flow and impair the growth of the paranasal sinus. As a consequence, mucosal ciliary activity decreases and bacterial invasion develops [6][7][8]. Additionally, previous studies stated that concha bullosa (pneumatized middle turbinate) adversely affects the paranasal sinus ventilation and mucociliary clearance in the middle meatus region [9].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates acceptance of the second hypothesis, A positive correlation between the extent of (A relationship between the contra lateral side and deviate side ) . (13,14,15) Financial Disclosure: There is no financial disclosure.…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Есть исследования, в которых была описана связь между объемом ОНП и степенью выраженности ДНП, но для разных пазух эта взаимосвязь была разной. В исследованиях, где ДНП классифицировалась по углу отклонения (слабая степень до 90°, умеренная от 90-150°, тяжелая степень более 150°), при умеренной и тяжелой степени ДНП наблюдались асимметрия и уменьшение объемов ипсилатеральных решетчатых [24], верхнечелюстных [25] и клиновидных пазух [26]. Есть другое мнение, что только умеренное отклонение ДНП влияет на объем ВЧП [27].…”
Section: цель работыunclassified
“…Есть другое мнение, что только умеренное отклонение ДНП влияет на объем ВЧП [27]. Исследования, включающие суммарно 869 обследуемых, показали, что на стороне выраженной деформации перегородки носа объем ВЧП был меньше, чем на контралатеральной стороне [28][29][30][31], где зачастую имелась СВ. При двусторонней СВ наблюдалось увеличение ВЧП с обеих сторон [2].…”
Section: цель работыunclassified